Code Switching and Code Mixing in the Communication of Arabic Language Education Master Students UIN Malang: A Sociolinguistic Study - Devi Rafika Sari; Riski Janu Saputra; Hafizaturrahmi (PT. Berkah Smart Academica, 2025)
Code switching is the phenomenon of changing the use of language or language variants in a conversation by a speaker, either between languages (e.g., from Indonesian to English) or between variations of the same language (e.g., from formal to informal language). Code switching usually occurs to facilitate communication, adjust to the situation, or show social identity. The aim of this research is, (1) to determine the form of code switching and code mixing that occurs in Arabic language education master students at UIN Maulana Malik Ibrahim Malang. (2) to determine what factors cause code switching and code mixing. This study uses a qualitative approach with a descriptive research type. The sample of this study was class F Arabic language education master students. The data collection technique used observation, after the data was collected it was analyzed using descriptive analysis techniques. The results of the data study show, (1) Code switching and external code mixing from Indonesian to Arabic or vice versa have 2 forms, namely oral and written communication. In oral communication, what occurs is code switching and code mixing between Indonesian and Arabic Fushah or Amiyyah or vice versa. In written communication in the WhatsApp group, code switching and code mixing occur between Indonesian and Arabic in the form of Arabic Fushah, Amiyyah, and Pegon. The code mixing that occurs is in the form of words, phrases, and also clauses. (2) The factors that cause code switching are speaker and interlocutor factors. Meanwhile, the factors that cause code mixing are role identification, education, and casualness (informality).